The interplay between strategic risk profiles and presentation format on managers' strategic judgments using the balanced scorecard - Cheng, Mandy M.; Humphreys, Kerry A.; Zhang, Yichelle Y. (Accounting, Organizations and Society, 2018)
Managers are increasingly aware that strategic judgments need to be made in the context of risk assessments. It has been proposed that strategic performance management systems, such as the balanced scorecard (BSC), offer a useful framework for integrating strategic risk and performance information to provide managers with a more comprehensive overview of their strategy. In this study, we conduct an experiment to investigate whether integrating strategic risk information in a BSC affects managers' responses to different strategic risk profiles when making strategy evaluation and recommendation judgments. Specifically, we provide strategic risk information either as a stand-alone list (a stand-alone approach), or incorporated in a BSC (an integrated approach). We also vary the risk profile of the strategy provided, by manipulating whether the strategy has relatively higher risks associated with performance drivers (high performance driver risks) or relatively higher risks associated with performance outcomes (high performance outcome risks). Our results show that managers make less favorable strategy evaluation and recommendation judgments with high performance driver risks than with high performance outcome risks when strategic risk information is integrated in a BSC, but not when the strategic risks are presented as a stand-alone list. While we find a significant difference in strategic risk profile effects between the two presentation formats for strategy recommendation judgments, this difference is not significant for strategy evaluation judgments. Overall, our study shows that how organizations choose to combine the reporting of strategic risk and performance information is important for managers making strategic judgments.